Hydrogeochemistry assessment of volcanic lakes in the Flores Island Protected Areas (Azores, Portugal) - Antunes,P. (2014)
Azorean lakes represent strategic freshwater resources and are subject to unprecedented levels of anthropogenic disturbance. The Flores Island lakes contribute 5% of the total water volume of aquatic systems in the Azores and are an important habitat for freshwater species. Sampled lakes are located inside maars structures. Lake Negra, with a depth of 115m, is the deepest lake. The lakes water is cold, with thermal stratification observed during sampling campaigns. pH has varied from 5.43 to 9.94 and they are very dilute waters. Aquatic systems waters are fresh and of the Na-Cl and Na-Ca-HCO3 types. It is possible to identify three major processes that control the hydrogeochemical evolution of the lake water studied here: (1) a marine sea salt input due to atmospheric transportation and deposition; (2) the hydrolysis of volcanic rock and; (3) a contribution of mineral water flowing through the rim of the crater. Aquatic systems have no direct interaction with seepage of magmatic fluids, a common process in Azores lakes. The highest decline in lake water quality is related to anthropogenic activities.